Moderasi Manacika Parisudha terhadap Pengaruh Skeptisme Profesional pada Deteksi Kecurangan - Agung Kresnandra, Anak Agung Ngurah; Anggara, I Wayan Gde Wahyu Purna (E-Jurnal Akuntansi, 2021)
This study aims to determine the effect of the moderating variable Manacika Parisudha on the effect of professional auditor skepticism on fraud detection. To achieve the research objectives, primary data was collected through the distribution of questionnaires that had passed the instrument test with 60 respondents holding internal supervisory positions such as internal auditors, accountants and taxation. This research uses quota sampling method. The hypothesis was tested using Moderated Regression Analysis (MRA). The results found that Auditor Professional Skepticism had a positive and significant effect on Fraud Detection¸ and Manacika Parisudha did not strengthen the positive influence of Professional Auditor Skepticism on Fraud Detection. Keywords: Auditor's Professional Skepticism; Manacika Parisudha; Fraud Detection.